THE EFFECT OF INVESTMENT DECISIONS, FUNDING DECISIONS AND DIVIDEND POLICY ON FIRM VALUE AT PT. UNILEVER INDONESIA TBK. YEAR 2014 TO 2023 - Elvia Desi, Dona (Qawwam : The Leader's Writing, 2025)
This study aims to determine how the effect of investment decisions, funding decisions and dividend policy on firm value at PT Unilever Indonesia Tbk. 2014 to 2025. By using secondary data in the form of company financial statements, multiple linear regression analysis, rdeterminant coefficient and hypothesis testing, the results show that partially investment decisions have a positive but insignificant effect on firm value, funding decisions have a positive and significant effect on firm value, dividend policy has a negative and insignificant effect on firm value. Simultaneously investment decisions, funding decisions and dividend policy have a significant effect on firm value with an influence of 96.7%.